Bacterial membrane disruption in Bacillus subtilis, Staphylococcus aureus and Escherichia coli by Cynodon dactylon extract - Syahriel Abdullah; Chong, Khim Phin; Januarius Gobilik (Universiti Putra Malaysia, 2014)
Cynodon dactylon is a type of perennial grass that possesses great medicinal values. It has been reported to possess great antibacterial activity against many Gram positive and negative bacteria. It is believed that most antibacterial compounds show great antibacterial mechanism through membrane toxicity effect. Electron microscope (EM) is a powerful tool in observatory analysis which offers capability to observe extremely small sample or structure up to micron size. In present study the effect of C. dactylon extract on Bacillus subtilis, Staphylococcus aureus and Escherichia coli cellular membrane was investigated using Scanning Electron Microscope (SEM). SEM observation revealed the disruption of bacterial membrane and caused complete lyse in B. subtilis and E. coli and S. aureus after treated with C. dactylon SPE extract which led to bacterial cell death.